Gastric and small intestinal traditional serrated adenomas: a detailed morphologic and immunohistochemical analysis - Kiremitçi, Saba; Ersöz, Cevriye Cansız; Savaş, Berna; Ensari, Arzu (Turkish Journal of Gastroenterology, 2020)
Background/Aims: TSAs, despite their low incidence in colorectum, may originate in other parts of gastrointestinal (GI) tract, including stomach and small intestine. Malignant transformation for upper GI TSAs has recently been reported in the literature. We, hereby, present a series of gastric and small intestinal TSAs with the aim to characterize their morphologic and immunophenotypic features as well as their neoplastic potential in a compartmental manner using digitalized images.Materials and Methods: The study comprised of 12 GI polyps with TSA features; 5 gastric and 7 small intestinal. Extent of characteristic features of TSA including eosinophilic cells, ectopic crypt foci (ECF), slit-like serration, foveolar epithelium, goblet cells, together with dysplastic/carcinomatous foci were assessed on digitalized H&E images and were used as reference for immunohistochemical analysis.Results: All polyps in the cohort contained eosinophilic cells as the most extensive morphologic feature followed by ECF and slit-like serration in decreasing order. Serrated dysplasia was more common in gastric polyps which more frequently showed neoplastic progression compared to intestinal ones. CK20 was the most widely expressed marker with a preference to eosinophilic cells while ECF were mostly negative. Ki67 showed the opposite pattern of CK20. MUC6 and MUC2 were selectively expressed in basal zone and goblet cells, respectively.Conclusion: Our results showed that presence of eosinophilic cells with pencillate nuclei commonly accompanied by ECF and slit-like serration are the defining features of gastric and small intestinal TSAs. They frequently harbour neoplastic foci, particularly in gastric location where serrated dysplasia seems to be more common.